The influence of parents’ perception on online education and training brand recognition - Xue, Biyun; Song, Ye (Frontiers in Psychology, 2022)
At present, the academic education of Chinese students is basically public education, but the quality training is mainly handed over to the market for training. Therefore, China's online education and training institutions have gradually developed under this demand. With the improvement of people's living standards, families have higher and higher requirements for children's education, expecting that children can be well improved in physical, mental and psychological aspects, and hoping that they will have their own advantages in the future competition. Therefore, this paper studies the influence of parents' perception on the brand recognition of online education and training. Through the analysis of dance online training institutions, the research shows that among the three categories, teachers' Graduation schools account for the highest proportion, with an average proportion of 47.07%, followed by teachers' grade certificates, with a proportion of 32.29%, and teachers' competition scores of 25.57%. Therefore, in the process of operation, online dance training institutions should meet the needs of parents to understand the professional level of teachers. Improve the service system of training institutions, improve the parent brand recognition and the number of customers of training institutions, further improve online education and training institutions, and provide them with improvement suggestions and measures for reference.